Photodynamic therapy for macular choroidal osteoma. Issue 4 (July 2022) - Scupola, Andrea; Ruggeri, Maria Ludovica; Sammarco, Maria Grazia; Pagliara, Monica Maria; Blasi, Maria Antonietta
Purpose: To report a case of macular choroidal osteoma treated with photodynamic therapy. Observations: A 34-years old woman with decreased visual acuity in her left eye came to our observation for assessment of an amelanotic choroidal tumor in the left eye. On the basis of ophthalmoscopic and echographic features the tumor was diagnosed as choroidal osteoma. Imaging examination revealed subretinal fluid involving the foveal area associated with alterations of outer neuroepithelial layers and photoreceptors without evidence of choroidal neovascularization. Foveal sparing standard fluence rate photodynamic therapy was performed. After treatment, subretinal fluid reabsorption and visual acuity recovery was noted with progressive restoration of foveal architecture. Due to the relapse of fluid and visual impairment, 1 year after treatment, a second PDT session was made using the same parameters and protocol of treatment. Despite a complete subretinal fluid reabsorption and visual acuity recovery the second treatment was complicated by the development of subretinal fibrosis. Conclusions: PDT is effective to induce subretinal fluid reabsorption and visual recovery in choroidal osteoma located in the macular area. However, the risk of possible complications related to the treatment have to be considered.